Workshop on Strengthening Social Science in the CGIAR: Summary Notes - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2010)
The one-day workshop on 27th March in Montpellier was organised by the Alliance of the CGIAR Centers, BMGF and the interim ISPC. The workshop was organised to follow up on the 2009 Stripe Study on Social Science in the CGIAR with the aim to stimulate the first high level discussion on ways to improve the state of social sciences in the CGIAR.